127-(2x+9)^3=(-1)^36x2
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Lời giải:
a)
Áp dụng BĐT Bunhiacopxky:
\((y-2x)^2\leq (16y^2+36x^2)(\frac{1}{16}+\frac{1}{9})=9.\frac{25}{144}\)
\(\Rightarrow \frac{-5}{4}\leq y-2x\leq \frac{5}{4}\Rightarrow \frac{15}{4}\leq y-2x+5\leq \frac{25}{4}\)
Vậy $A_{\min}=\frac{15}{4}$ và $A_{\max}=\frac{25}{4}$
b)
Áp dụng BĐT Bunhiacopxky:
\((2x-y)^2\leq (\frac{x^2}{4}+\frac{y^2}{9})(16+9)=25\)
\(\Rightarrow -5\leq 2x-y\leq 5\Leftrightarrow -7\leq 2x-y-2\leq 3\)
Vậy $B_{min}=-7; B_{\max}=3$
\(a,\Leftrightarrow6x-9+4-2x=-3\Leftrightarrow4x=2\Leftrightarrow x=\dfrac{1}{2}\\ b,\Leftrightarrow\left(x-2021\right)\left(x-6\right)=0\Leftrightarrow\left[{}\begin{matrix}x=2021\\x=6\end{matrix}\right.\\ c,\Leftrightarrow\left(2x-3-6x\right)\left(2x-3+6x\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}-3-4x=0\\8x-3=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=-\dfrac{3}{4}\\x=\dfrac{3}{8}\end{matrix}\right.\)
\(1+12x+36x^2=\left(6x\right)^2+2.6x.1+1^2=\left(6x+1\right)^2\)
a) (−27). 1011 − 27. (−12) + 27. (−1)
= (-27). (1011 - 12 + 1)
= (-27). 1000 = -27 000
b) (−9). (−9). (−9) + 103 + 9.3
= (-9). 3 + 103 + 9.3
= 9.3 - 9.3 + 103
= 0 + 103 = 103
c) (−157). (127 − 316) − 127. (316 − 157)
= (-157). 127 - 316. (-157) - 127.316 - 127. (-157)
= (-157). 127 + 316. 157 - 127. 316 + 127.157
= (127.157 - 157.127) + (316. 157 - 127.316)
= 0 + (157 - 127). 316
= 0 + 30. 316
= 9480
⇔127-(2x+9)3=2
⇔(2x+9)3=125
⇔(2x+9)3=53
⇒2x+9=5
⇔2x=-4
⇔x=-2
Vậy x=-2